Varied, unprecedented dermatologic manifestations of hypovitaminosis D –A case series - Sarkar, Amit; Bandyopadhyay, Rajat; Bhowmik, Kalyan Kumar; Chakrabarti, Arpan; Mukhopadhyay, Neelakash; Paul, Arnab (Asian Journal of Medical Sciences, 2023)
Vitamin D deficiency is endemic in India. Hypovitaminosis D not only results in musculoskeletal disorders but also affects extraskeletal systems. In this article, we describe three interesting patients suffering from hypovitaminosis D with dermatologic manifestations of erythema nodosum, heel fissures, and palmar hyperhidrosis. All the three cases responded well to treatment with vitamin D. Similar cases have not been reported earlier.